Review of Tanker Safety after the Introduction of OPA 90 - Papanikolaou, Apostolos; Eliopoulou, Eleftheria; Hamann, Rainer (SPOUDAI Journal of Economics and Business, 2013)
The present study focuses on a comprehensive analysis of recorded accidents of medium and large oil tankers (deadweight over 20,000 tonnes), which occurred after the introduction of OPA90 and until today. Raw casualty data was reviewed and re-analysed in order to produce appropriate statistics useful for the implementation of risk-based assessment methodologies. The main outcome of the presented study is the identification of significant historical trends and of quantitative characteristics of individual categories of tanker accidents, like overall accidental frequencies per ship year, frequencies of each major accident category and per tanker ship size, ship type/design and age, the degree of accidents’ severity and the oil spill tonne rates per ship year. Therefore this study is a valuable source of information for the assessment of the effectiveness of current IMO regulations, classification society rules and tanker industry’s practice. JEL Classifications: L9.